2020
DOI: 10.3390/ijms21030914
|View full text |Cite
|
Sign up to set email alerts
|

SERPINA1 Peptides in Urine as A Potential Marker of Preeclampsia Severity

Abstract: Preeclampsia (PE) is a multisystem disorder associated with pregnancy and its frequency varies from 5 to 20 percent of pregnancies. Although a number of preeclampsia studies have been carried out, there is no consensus about disease etiology and pathogenesis so far. Peptides of SERPINA1 (α1-antitrypsin) in urine remain one of the most promising peptide markers of PE. In this study the diagnostic potential of urinary α1-antitrypsin peptides in PE was evaluated. The urinary peptidome composition of 79 pregnant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…Furthermore, A1AT-OE or A1AT administration increases the migration and invasion of human umbilical vein endothelial cells from women with PE [ 19 ]. Conversely, it has been reported that A1AT expression is high in placentas from patients with PE [ 24 ] and that the urinary A1AT concentration is high in women with PE [ 5 , 25 , 26 ]. Our data suggest that A1AT regulates cell motility via ER stress and HTRA1 expression in trophoblast cells, and that dysregulation may be associated with complications of pregnancy, including PE ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, A1AT-OE or A1AT administration increases the migration and invasion of human umbilical vein endothelial cells from women with PE [ 19 ]. Conversely, it has been reported that A1AT expression is high in placentas from patients with PE [ 24 ] and that the urinary A1AT concentration is high in women with PE [ 5 , 25 , 26 ]. Our data suggest that A1AT regulates cell motility via ER stress and HTRA1 expression in trophoblast cells, and that dysregulation may be associated with complications of pregnancy, including PE ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a reduction of A1AT protein in endometriosis-like lesions exacerbates the inflammatory response in mice [ 4 ]. It has been shown that urinary A1AT may represent a marker of the severity of PE [ 5 ]. Furthermore, A1AT may reduce organ damage in a serine protease activity-independent fashion [ 6 ], although interaction with high-temperature requirement A serine peptidase 1 (HTRA1) may be involved [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nineteen of these showed high potential for PE prediction as they were consistently higher or lower in PE, including ceruloplasmin, serpin A1, serpin A5, C3, ALB, TF and HBB. Starodubtseva et al reported that the estimation of serpin A1 peptides in urine was also related to the severity of PE [39]. Placental growth factor (PlGF), a proangiogenic protein commonly used for the prediction of PE and other placentalmediated outcomes of pregnancy is also predictive of PE and PE-related adverse outcomes when measured in urine [17,23,40].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it has been found that unique peptides derived from α-antitrypsin, type I collagen, type III collagen, and urinary modulin can be used as early diagnostic indicators of PE (21). Furthermore, it has been emphasized that SERPINA1 peptide in urine remains one of the most promising polypeptide markers of PE (21). Taken together, these studies suggest that peptides may be a useful potential target for the prevention and treatment of PE.…”
Section: Introductionmentioning
confidence: 93%
“…It has been identified that there are 35 statistically different polypeptides in the placentas of PE patients and normal pregnancies (20). At the same time, it has been found that unique peptides derived from α-antitrypsin, type I collagen, type III collagen, and urinary modulin can be used as early diagnostic indicators of PE (21). Furthermore, it has been emphasized that SERPINA1 peptide in urine remains one of the most promising polypeptide markers of PE (21).…”
Section: Introductionmentioning
confidence: 99%